Physical Activity Patterns Among Women and Men During Pregnancy and 8 Months Postpartum Compared to Pre-pregnancy: A Longitudinal Study - Sjögren Forss, Katarina; Stjernberg, Louise (Frontiers in Public Health, 2019)
Background: Realizing the essential prerequisite of regular physical activity (PA) it is essential to have knowledge about how different life change events may influence individual's participation. Many studies have documented that pregnancy and the transition to parenthood are life change events associated with decreased PA among women however, the examination of changes of PA in the male parent during this major life change event has been largely neglected in scientific literature and a significant research gap can be found. In the light of this, this longitudinal study aimed to follow changing PA patterns among women and men during pregnancy and 8 months postpartum compared to pre-pregnancy. Methods: In this study, 123 women and 112 men (partners of the women) that lived in the municipality of Karlskrona, Sweden, were included. Data were collected between 2008 and 2010. The self-reported amount of PA performed outdoors and indoors before pregnancy throughout the entire pregnancy, and 8 months postpartum, were measured. Results: We found similar changes in PA patterns among both women and men during pregnancy and 8 months postpartum when compared to pre-pregnancy. In almost all the activities studied except for walking/strolling, a significant decline was found. Conclusions: Our findings contribute new knowledge about changes in men's PA patterns from pre-pregnancy to pregnancy and postpartum. As couples seem to change activity patterns similarly, it is important to promote family-based PA initiatives and encourage couples to be active together during pregnancy and postpartum.